CompSupport: A series of unfortunate events. Issue 1 (May 2020) - Al Natour, Sameh
CompSupport Inc. was a leader of online support services for personal computers and devices. After a brief period operating in a B2C channel, the company shifted and refined its focus to two primary customer segments: Internet service providers and corporate accounts. CompSupport's key mandate was to improve their customer's helpdesk operations through outsourcing in order to achieve two goals: cost reduction and improved customer service. In May 2017, the lack of liquidity meant that the company would be unable to make its next pay period without an additional injection of funds. The company arrived at a crossroads, and a decision had to be made. The alternatives consisted of two buyout options and a merger opportunity. This case study evaluates CompSupport's state at the time of the decision, and highlights the events that took place prior to the decision period that may have contributed to the company's problems.